(untitled) (Research, Society and Development, 2021)
The purpose of this review is to demonstrate the findings on the use of natural compounds as preservatives in meat and meat products as a healthier and safer alternative compared to the use of synthetic preservatives. Due to its biological composition, meat and its derivatives are susceptible to spoilage, a process that can be delayed with the use of synthetic food preservatives. However, it is known that some products can trigger undesirable effects on consumer health. In recent years, there has been a greater demand for products obtained naturally or directly from a biological organism without laboratory interference in their composition, in order to reduce risks to the consumer. The most promising compounds belong to the groups of phenolic and flavonoid compounds, which have a proven, positive effect on oxidation and microbial development. Findings on the use of natural compounds as preservatives in meat and meat products demonstrate an alternative to increased shelf life without risking consumer health.